Self-adaptive pyroptosis-responsive nanoliposomes block pyroptosis in autoimmune inflammatory diseases - Kaiwang Xu; Huang Yang; Jinghua Fang; Kaijie Qiu; Haotian Shen; Guanrui Huang; Qiangqiang Zheng; Canlong Wang; Tengjing Xu; Xinning Yu; Jiajie Wang; Yunting Lin; et al. (Bioactive Materials, 2024)
Nanoliposomes have a broad range of applications in the treatment of autoimmune inflammatory diseases because of their ability to considerably enhance drug transport. For their clinical application, nanoliposomes must be able to realize on-demand release of drugs at disease sites to maximize drug-delivery efficacy and minimize side effects. Therefore, responsive drug-release strategies for inflammation treatment have been explored; however, no specific design has been realized for a responsive drug-delivery system based on pyroptosis-related inflammation. Herein, we report a pioneering strategy for self-adaptive pyroptosis-responsive liposomes (R8-cardiolipin-containing nanoliposomes encapsulating dimethyl fumarate, RC-NL@DMF) that precisely release encapsulated anti-pyroptotic drugs into pyroptotic cells. The activated key pyroptotic protein, the N-terminal domain of gasdermin E, selectively integrates with the cardiolipin of liposomes, thus forming pores for controlled drug release, pyroptosis, and inflammation inhibition. Therefore, RC-NL@DMF exhibited effective therapeutic efficacies to alleviate autoimmune inflammatory damages in zymosan-induced arthritis mice and dextran sulfate sodium-induced inflammatory bowel disease mice. Our novel approach holds great promise for self-adaptive pyroptosis-responsive on-demand drug delivery, suppressing pyroptosis and treating autoimmune inflammatory diseases.